Circulating microRNA Expression Profiling Identifies miR-125a-5p Promoting T Helper 1 Cells Response in the Pathogenesis of Hashimoto's Thyroiditis - Liu, Yingzhao; Ding, Xiangmei; Xiong, Si; Wang, Xuehua; Tang, Xinyi; Wang, Li; Wang, Shengjun; Peng, Huiyong (Frontiers in Immunology, 2020)
MicroRNAs (miRNAs) have emerged as key regulators of cellular processes by suppressing target mRNAs at the posttranscriptional level. However, little is known regarding the expression of miRNAs in peripheral blood mononuclear cells (PBMCs) from Hashimoto’s thyroiditis (HT) patients. Therefore, thirty-eight HT patients and thirty-six healthy volunteers were enrolled in this study to identify HT-mediated changes in miRNA expression. Over one thousand dysregulated miRNAs and their biological functions in the HT patients were identified. Among them, miR-125a-5p expression was upregulated and inversely correlated with low levels of MAF, a transcription factor that inhibits Th1 cells activity and the production of IFN-γ. Luciferase assay results demonstrated that MAF is a direct target gene of miR-125a-5p. Moreover, the proportion of circulating Th1 cells and the transcript levels of IFN- were increased in the HT patients. MiR-125a-5p expression positively correlated with the proportion of circulating Th1 cells and the serum concentrations of anti-thyroperoxidase antibodies in the HT patients. Interestingly, knockdown of miR-125a-5p in CD4+ T cells resulted in an elevated level of MAF but decreased the proportion of Th1 cells and the transcript level of IFN-γ in vitro. Furthermore, upregulated miR-125a-5p and IFN-γ levels and downregulated MAF expression were detected in thyroid tissues from HT patients. Receiver operating characteristic (ROC) curves suggested that miR-125a-5p has a crucial role in the HT. Our results demonstrate that the elevated levels of miR-125a-5p contribute to the Th1 cells response in the HT patients and may be involved in the pathogenesis of HT.